Dynamics of serological and bacterial responses among patients with melioidosis - Janaki a/p Arumugam (Kulliyyah of Medical Sciences, International Islamic University Malaysia, 2016)
Melioidosis is an important public health disease caused by the Gram-negative bacteria Burkholderia pseudomallei which is endemic in Southeast Asia and northern Australia. The disease is highly associated with age, occupation, rainfall and predisposing chronic diseases, such as diabetes mellitus. Early laboratory diagnosis is very crucial as the disease carries a very high mortality rate and requires prolonged antimicrobial therapy to achieve full clinical resolution of infection. This study was attempted to clarify the dynamics of serological responses and bacterial persistence among melioidosis patients and their correlation with the clinical outcome. In this study 40 bacteriologically confirmed melioidosis patients from the states of Pahang and Terengganu were recruited after obtaining their informed consent together with another 2 control groups, 40 each, of patients with or without other infections. Bacterial blood culture was used to confirm melioidosis. Serological tests by indirect immunofluorescent antibody test (IFAT) for specific IgG and IgM were evaluated for their sensitivity and specificity after determining the cut-off value for each by the receiver operating characteristic (ROC) curve analysis. Specific IgM and IgG antibody titers and bacterial presence were tested in patients on days 1, 8, 15, 30, 60 and 90 of diagnosis using (IFAT) and real-time PCR (qPCR) respectively. The estimated optimal cut-off value(s) for IFAT-IgM was (20) and IFAT-IgG (80). These cut-off value(s), especially applicable to endemic regions, show the best balance between sensitivity and specificity, however they were quite modest as the sensitivity and specificity for IgM assay was 72.5% and 80% respectively and for IgG 65% and 87.5% respectively. There were significant dynamic changes of the geometrical mean titers of IgM and IgG over the 3 months period of study. The levels of specific IgM and IgG were increased by 2 and 4 folds respectively on day 8 and reached a maximum level together on day 15. The IgG antibody titers were several folds higher than IgM as early as day 8, and though they tended to decline after day 30 but persisted at relatively high level until the end of study at day 90. Among melioidosis patients, survivors had superior serological responses to deceased one, especially on day 1 which probably contributed to the more effective clearance of infection. In conclusion, the IFAT assay for specific IgM and IgG occupies a modest place as both a diagnostic and prognostic test. Nevertheless, qPCR is of more diagnostic value, having high specificity and a sensitivity that probably can be improved mainly by proper timing of the blood sampling before antibiotic treatment and also by either increasing the volume of extracted blood and/or by decreasing the volume of DNA elution buffer to increase the concentration of extracted DNA. In retrospect, the qPCR may be useful in monitoring bacterial persistence after treatment, which may indicate unsatisfactory response to the antibacterial therapy thus requiring its re-evaluation